2022
DOI: 10.1029/2021je007063
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Evolution in Metallic Asteroids: Implications for the Origin and Thermal History of Asteroid 16 Psyche

Abstract: Some M‐type asteroids have measured bulk densities much lower than expected based on their metal‐rich surfaces. In particular, the density of the largest M‐type asteroid 16 Psyche would require a bulk porosity of ∼52 vol% if it has a pure iron composition. We determine that a pure iron Psyche must have cooled to and remained below 800 K to maintain sufficient porosity for that porosity to persist until present. Iron bodies smaller than Psyche could preserve long‐lived high porosities (>40%), yet even the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The IVA irons are inferred to sample materials from different depths of its parent body, from near‐surface to central regions, which is typically inferred as evidence for the catastrophic breakup of their parent body. The cloudy‐zone micro‐structures of the IVA irons suggest that they were still inside their parent body at temperatures of ∼500–600 K. This implies that the disruption likely occurred at temperatures below ∼500 K, which is probably low enough for the body to remain porous after the disruption event (Nichols‐Fleming et al., 2022). Although the IVA irons are not necessarily from Psyche, their thermal and collisional history implies that disruption may occur after the cooling of Psyche‐sized metallic bodies.…”
Section: Implications For Psychementioning
confidence: 99%
See 2 more Smart Citations
“…The IVA irons are inferred to sample materials from different depths of its parent body, from near‐surface to central regions, which is typically inferred as evidence for the catastrophic breakup of their parent body. The cloudy‐zone micro‐structures of the IVA irons suggest that they were still inside their parent body at temperatures of ∼500–600 K. This implies that the disruption likely occurred at temperatures below ∼500 K, which is probably low enough for the body to remain porous after the disruption event (Nichols‐Fleming et al., 2022). Although the IVA irons are not necessarily from Psyche, their thermal and collisional history implies that disruption may occur after the cooling of Psyche‐sized metallic bodies.…”
Section: Implications For Psychementioning
confidence: 99%
“…If Psyche is a metallic rubble pile, its formation history should include both a mantle‐stripping event and a porosity‐adding event. Mantle stripping is likely associated with one or repeated hit‐and‐run collisions (e.g., Asphaug & Reufer, 2014; Asphaug et al., 2006), which likely occurred in the first few million years following solar system formation, in which case the core cannot cool fast enough to preserve porosity against viscous compaction (Nichols‐Fleming et al., 2022). If a disruptive collision occurred after the exposed core had sufficiently cooled (e.g., tens of millions of years after solar system formation), the collision fragments could remain sufficiently cold, since heating from disruptive collisions is thought to be small (Keil et al., 1997; Love & Ahrens, 1996).…”
Section: Implications For Psychementioning
confidence: 99%
See 1 more Smart Citation
“…This inconsistency may be understandable if Psyche is a rubble-pile asteroid having a very high porosity (>∼50%). Also, Nichols-Fleming et al (2022) recently indicated that Psyche might be difficult to reconcile with a fully metallic structure by showing that high porosity (∼40%) cannot be sustainable owing to the porosity removal by thermal evolution. They found that a Psyche-sized body must cool down below 800 K prior to porosity-adding events (i.e., disruptive impacts) to maintain sufficient porosity (∼40%) until the present.…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistency may be understandable if Psyche is a rubble-pile asteroid having a very high porosity (> ∼50%). Also, Nichols-Fleming et al (2022) recently indicated that Psyche might be difficult to reconcile with a fully metallic structure by showing that high porosity (∼40%) cannot be sustainable due to the porosity removal by thermal evolution. They found that a Psyche-sized body must cool down below 800 K prior to porosity-adding events (i.e., disruptive impacts) to persist the sufficient porosity (∼40%) until the present.…”
mentioning
confidence: 99%